2016
DOI: 10.5194/hess-20-93-2016
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatological influences on recently increased droughts in China's largest freshwater lake

Abstract: Abstract. Lake droughts are the consequence of climatic, hydrologic and anthropogenic influences. Quantification of droughts and estimation of the contributions from the individual factors are essential for understanding drought features and their causation structure. This is also important for policymakers to make effective adaption decisions, especially under changing climate. This study examines Poyang Lake, China's largest freshwater lake, which has been undergoing drastic hydrological alternation in the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…The Poyang Lake basin has invaluable services in biodiversity maintenance, social and ecological benefits, flood control, and drought prevention (Hong et al , ; Liu and Wu, ; Wagner et al , ). It is an important region to the Global Change and Terrestrial Ecosystems project of the International Geosphere‐Biosphere Programme (IGBP) (Canadell et al , ) and internationally important wetlands (The Ramsar Convention, ).…”
Section: Study Area and Datamentioning
confidence: 99%
“…The Poyang Lake basin has invaluable services in biodiversity maintenance, social and ecological benefits, flood control, and drought prevention (Hong et al , ; Liu and Wu, ; Wagner et al , ). It is an important region to the Global Change and Terrestrial Ecosystems project of the International Geosphere‐Biosphere Programme (IGBP) (Canadell et al , ) and internationally important wetlands (The Ramsar Convention, ).…”
Section: Study Area and Datamentioning
confidence: 99%
“…For example, Dai, Du, Li, Li, and Chen () reported that extreme drought (45%) contributed to the water flux loss more than the TGD impoundment (9%) in 2006. Y. Liu and Wu () also demonstrated that the hydroclimatic influences (e.g., reduced precipitation and inflow) largely contributed to Poyang Lake droughts but not the responsibility of TGD impoundments. Nevertheless, Lai et al () also found that the effects of the TGD on downstream rivers and lakes will be intensified in future when many ongoing and planned large‐scale dams located in the upstream tributaries in the Yangtze River.…”
Section: Introductionmentioning
confidence: 99%
“…The basin not only provides a graceful natural ecological environment for the life of approximately 50 million people but also serves as an important national food base (Liu et al, ). It includes the largest freshwater lake (i.e., Poyang Lake) in China and plays a significant role in many aspects, such as maintaining biodiversity, socioeconomical and ecological activities, flood control, and drought prevention (Hong et al, ; Liu & Wu, ; The Ramsar Convention, ; Wagner et al, ). However, in recent decades, due to the impacts of climate changes and anthropogenic actives, the basin has frequently suffered from extreme hydrological events (e.g., drought and flood; Shankman et al, ; Ye et al, ; Zhang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, in recent decades, due to the impacts of climate changes and anthropogenic actives, the basin has frequently suffered from extreme hydrological events (e.g., drought and flood; Shankman et al, ; Ye et al, ; Zhang et al, ). In comparison to the year before 2000, the current hydrological droughts in Poyang Lake have higher frequency, more severity, and longer duration (Liu & Wu, ). In addition, the basin is one of the most active regions where droughts occur (Herrera‐Estrada et al, ).…”
Section: Methodsmentioning
confidence: 99%